2019
DOI: 10.1080/17445302.2019.1661628
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the design requirement against blast load for ship superstructure

Abstract: This paper attempts to rationalise, and assess, the existing design requirement for the sizing of the outer plating of a ship superstructure against an external air blast. First, a review of the current design guideline, specifically on how the blast load parameters were specified by the Rules and Regulations of Lloyd's Register and the assumptions behind the use of the scantling equation, is provided by way of a design case study. Next, a non-linear SDOF model that incorporates a new plastic membrane phase is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…5; whereas the results predicted using a 16 × 16 mm 2 mesh indicates a different fracture behaviour. It is hardly surprising that the predictions for damage evolution is mesh-dependent -due to the stress singularities at the sharp corner of the square holes -as was previously noted in [9,[43][44][45]. Using a different failure criterion based on critical plastic work, Aune et al [2], too, found that the predicted damage evolution of the air-blast loaded ductile plate with square holes also depends upon the mesh size.…”
Section: Mesh Sensitivity Studymentioning
confidence: 80%
“…5; whereas the results predicted using a 16 × 16 mm 2 mesh indicates a different fracture behaviour. It is hardly surprising that the predictions for damage evolution is mesh-dependent -due to the stress singularities at the sharp corner of the square holes -as was previously noted in [9,[43][44][45]. Using a different failure criterion based on critical plastic work, Aune et al [2], too, found that the predicted damage evolution of the air-blast loaded ductile plate with square holes also depends upon the mesh size.…”
Section: Mesh Sensitivity Studymentioning
confidence: 80%